Generation of utterances based on the turns «N-дно» and «reach a new low» in modern speech: on the issue of stability and variability of the component structure of a phraseological unit - E. I. Budaragina (Вестник Самарского университета: История, педагогика, филология)
The subject of this research is the characteristics of phraseological units, specifically their stability and reproducibility. The aim of this article is to demonstrate that these characteristics are not essential for identifying phraseological units. The study is based on a functional-semantic approach to phraseology (V.N. Teliya and Yu.P. Solodub). The material for analysis is composed of phraseological expressions derived from the phrases «reach a new low» and «N-дно». These expressions were collected from the speech of various speakers, including journalists, bloggers, politicians, and writers. Using discourse analysis, the grammatical variants and semantic transformations of these units were examined, particularly those related to the intensity category. The following conclusions were reached: the use of phraseological units often involves creativity, the variety of forms does not hinder the identification of phraseological variants as a unified whole, if there is a common image, based on, for example, the realization of a single cognitive metaphor, stability and reproducibility in the study of phraseological units should be attributed to substantive categories, rather than formal ones, when discussing the stability of phraseological units, it is important to take into account the stability of the core prototype, which allows for the unification of lexical-grammatical variants within a single phraseological unit.